153k views
3 votes
2 ln(x + 2) − ln(−x) = 0

User Chimera
by
4.9k points

1 Answer

3 votes

Answer:


x=-1

Explanation:

Rewrite the equation using the next propierties:


log((1)/(x) )=-log(x)


ylog(x)=log(x^(y) )


log(x*y)=log(x)+log(y)


ln((x+2)^2)+ln((-1)/(x) )=0\\ln(((x+2)^2)/(-x))=0

Cancel logarithms by taking exp of both sides:


((x+2)^2)/(-x) =e^(0) =1

Multiplying both sides by -x and factoring:


x^(2) +5x+4=0

Factoring:


(x+1)(x+4)=0

The solutions are:


x=-1\hspace{3}or\hspace{3}x=-3

Evaluating x=-4


2ln(-2)-(4)=0

This is an absurd because ln(x) is undefined for
x\leq 0

Evaluating x=-1


2ln(1)-ln(1)=0\\0-0=0

Which is correct, hence the solution is:


x=-1

User Draupnie
by
4.3k points